Pengaruh Faktor Yang Mempengaruhi Beban Kerja Terhadap Kinerja Karyawan (Studi Divisi Penjualan PT XYA, Jawa Barat): - Mardianti, Febri (International Journal Administration, Business & Organization, 2021)
Human resources are the driving force of the organization to achieve effective and efficient goals. To improve the organization's ability to face increasingly fierce business competition, it requires the ability of human resources that can compete. However, what is still an obstacle in human resources is employee performance. Generally, the service and manufacturing sectors face employee performance problems. PT XYZ is a garment company that produces baby equipment from the fabric manufacturing process to the distribution of finished goods. The high workload occurred in the sales division which was evident from the results of the performance assessment from year to year which decreased by approximately 10%. Not to mention the complaint of lack of time to be with family because of work. The researcher used a quantitative descriptive method which was tested on 114 respondents using a simple random sampling technique. It was found that there was a weak correlation. The contribution value of Workload to employee performance is 15% and the other 85% is influenced by other factors.